Executive Control of Language in the Bilingual Brain: Integrating the Evidence from Neuroimaging to Neuropsychology - Hervais-Adelman, Alexis G.; Moser-Mercer, Barbara; Golestani, Narly (Frontiers in Psychology, 2011)
In this review we will focus on delineating the neural substrates of the executive control of language in the bilingual brain, based on the existing neuroimaging, intracranial, transcranial magnetic stimulation and neuropsychological evidence. We will also offer insights from ongoing brain imaging studies into the development of expertise in multilingual language control. We will concentrate specifically on evidence regarding how the brain selects and controls languages for comprehension and production. This question has been addressed in a number of ways and using various tasks, including language switching during production or perception, translation and interpretation. We will attempt to synthesise existing evidence in order to bring to light the neural substrates that are crucial to executive control of language.